1997
DOI: 10.2307/1592142
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Chicken Reproductive Tissues and Forming Eggs Is Not Unique to Salmonella enteritidis

Abstract: Experiments were conducted in which Salmonella enteritidis Phage Type 8, Phage Type 2, and RDNC (reaction does not conform) or three isolates of Salmonella typhimurium of diverse origin were fed to adult laying hens to determine if S. enteritidis has a selective advantage over S. typhimurium, which is now rarely isolated from chicken eggs, in its capacity to invade reproductive tissues. The results revealed that S. enteritidis and S. typhimurium may be equal in their potential to colonize the tissues of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 20 publications
4
51
1
Order By: Relevance
“…Vertical transfer of infections from breeding hens to progeny has been an important aspect of the epidemiology of Salmonella species infections within the poultry industry [1,7,8,12,30].…”
mentioning
confidence: 99%
“…Vertical transfer of infections from breeding hens to progeny has been an important aspect of the epidemiology of Salmonella species infections within the poultry industry [1,7,8,12,30].…”
mentioning
confidence: 99%
“…As the follicles are particularly rich in nutrients, Salmonella grows extensively in them at a chicken body temperature of 42 °C, and this can lead to degeneration of the contaminated follicle before the production of the egg (Gantois et al, 2009). In studies involving experimental infections of laying hens, the presence of Salmonella in the ovaries did not necessarily correspond to the production of contaminated egg contents (Barrow and Lovell, 1991;Keller et al, 1997).…”
Section: Primary Contaminationmentioning
confidence: 99%
“…Studies have shown that some S. Enteritidis phage types (PTs) are more invasive than others (Hinton et al, 1990;Roy et al, 2001), but other similarly designed studies could not identify any difference in the invasiveness or colonisation ability between different phage types (Barrow, 1991). Despite its peculiar affinity for the reproductive tract of hens, S. Enteritidis is not the only serotype able to colonise ovaries and oviducts and contaminate forming eggs (Keller et al, 1997;Okamura et al, 2001a;Gast et al, 2004;Gantois et al, 2008).…”
Section: Factors Influencing Salmonella Pathogenesis In Chickensmentioning
confidence: 99%
See 2 more Smart Citations